Evaluation of a Bacillus thuringiensis isolate-based formulation against the pod borer, Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) - Thameur Bouslama; Ikbal Chaieb; Ali Rhouma; Asma Laarif (Egyptian Journal of Biological Pest Control, 2020)
Abstract The present study focuses on the evaluation of the potential of a Tunisian Bacillus thuringiensis (Bt) isolate named Hr1, isolated from dead and diseased pod borer, Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) larvae under laboratory and field semi-controlled conditions. The bacterial strain Hr1 showed an insecticidal activity against the pest’s neonates in comparison to the spinosad-based insecticide (Tracer 240 SC®) during bioassays under laboratory conditions. A carboxymethyl cellulose-talc (CMC-talc)-based formulation of the Bt isolate was prepared to evaluate the potential of the bacterium on tomato plants infested with H. armigera under semi-controlled field conditions with and without rain simulation. The results showed the efficacy of the formulation than the spinosad-based insecticide and the treatment with unformulated bacterium. The results also showed the persistence of Bt isolate activity even after rain-wash than the treatment with unformulated bacterium.